Analyzing the Digital Transformation Competence of Vietnamese Students Using Exploratory Factor Analysis (EFA) - Do, Thi Thanh Tam; Nguyen, Thi Thu Thuy; Nguyen, Thi Van Trang (INTI International University, 2024)
In Vietnam, digital transformation has been taking place strongly in all fields, especially education. Universities are very interested and focused on promoting digital transformation activities at their facilities. Students are individuals who participate and directly benefit from this process. The question is how competent students are when participating in digital transformation at the institution. This article focuses on researching the digital transformation competency of Vietnamese students in general, and at Commerce University in particular. From there, it provides educational institutions with the perspective of the digital transformation competency of students. Especially, based on experiments conducted with 405 students at the Universities of Commerce, the research group applied the Exploratory Factor Analysis (EFA) method and multiple linear regression to identify seven factors influencing digital transformation competence: "Interest", "Usefulness", "Importance", "Personal capacity", "Relationship", "University" and these seven factors explained 71.7% of the variation in digital transformation competence. In summary, the research provides support for educational institutions to develop plans for enhancing the digital transformation competency of students in general and at Thuongmai University in particular.